Turning the Tap: Conformational Control of Quantum Interference to Modulate Single‐Molecule Conductance. Issue 52 (31st October 2019) - Jiang, Feng; Trupp, Douglas I.; Algethami, Norah; Zheng, Haining; He, Wenxiang; Alqorashi, Afaf; Zhu, Chenxu; Tang, Chun; Li, Ruihao; Liu, Junyang; Sadeghi, Hatef; Shi, Jia; et al.
Abstract: Together with the more intuitive and commonly recognized conductance mechanisms of charge‐hopping and tunneling, quantum‐interference (QI) phenomena have been identified as important factors affecting charge transport through molecules. Consequently, establishing simple and flexible molecular‐design strategies to understand, control, and exploit QI in molecular junctions poses an exciting challenge. Here we demonstrate that destructive quantum interference (DQI) in meta ‐substituted phenylene ethylene‐type oligomers ( m ‐OPE) can be tuned by changing the position and conformation of methoxy (OMe) substituents at the central phenylene ring. These substituents play the role of molecular‐scale taps, which can be switched on or off to control the current flow through a molecule. Our experimental results conclusively verify recently postulated magic‐ratio and orbital‐product rules, and highlight a novel chemical design strategy for tuning and gating DQI features to create single‐molecule devices with desirable electronic functions. Abstract : Let it flow : The change of the conformation and location of a methoxy group at different positions of a molecular junction can serve as a molecular tap, which will precisely control the on/off state of the system regarding electrical conductance. The approach offers a simple way to control room‐temperature charge transport at the single‐molecule scale.